The Relationship Between Insulin Resistance and Polycystic Ovary Syndrome in Libyan Women - Maryouma Aghil; Rehab El-Megrabi; Hana Alfaghi; Raniya Alrakhees (Khalij-Libya Journal of Dental and Medical Research, 2025)
Polycystic ovary syndrome (PCOS) is a heterogeneous endocrine disease that is common in women of reproductive age and is usually caused by androgen excess and ovarian dysfunction. It is often accompanied by insulin resistance (IR) and some manifestations such as hirsutism and fertility problems. The current study was conducted to evaluate the prevalence of polycystic ovary syndrome and its relationship to insulin resistance among Libyan women, Tripoli. This study included 69 patients: 52 diagnosed with PCOS and 17 control women between the ages of 20 and 40. The study was conducted over three months, from January 2024 to March 2024, at Nour Al Hayat Fertility Hospital in Tripoli. a structured questionnaire was utilized to gather data on patient demographics, such as insulin resistance values, HbA1c levels, and various hormone levels, including TSH, FSH, Prolactin, and Testosterone. A 2 ml venous blood sample was collected from each patient for analysis. Insulin and fasting glucose levels were measured using two different assays to calculate the equation: Insulin FBS /450. Statistical analysis was performed using IBM SPSS version 22 software. The prevalence of polycystic ovary syndrome was 75%, compared to the control group, 25%. Furthermore, there was a significant increase in HOMA IR, HbA1c, Prolactin, and Testosterone levels (p < 0.05), as well as in FSH and TSH levels in the PCOS group compared to the control (P > 0.05). The results also showed that insulin resistance, HOMA IR, was positively correlated with HbA1c levels among both study groups (p < 0.05). In conclusion, Insulin resistance is a common feature of women with PCOS. This study highlights the importance of Insulin resistance and hyperandrogenism, which appear to be interrelated key factors in the pathogenesis of PCOS. Addressing insulin resistance can help improve symptoms and outcomes for individuals with PCOS.